Legal issues in adolescents’ rights under medical treatment as a constituent of right to health (2018)
The paper intends to contribute in facilitating the implementation of adolescents’ right within the myriad instances of daily decision making by the medical personnel which touch and concern the health of the adolescents. This paper has provided a comprehensive and detailed account of the law and practice of adolescents’ rights as it relates the patient, parents, and medical personnel showing that none of them has absolute power when it comes to medical treatment. It is concluded that the adolescent rights do not prevent interventions that will protect the adolescent front adverse health consequences